Lateral root morphogenesis is dependent on the mechanical properties of the overlaying tissues - Lucas, Mikael; Maizel, Alexis (Proceedings of the National Academy of Sciences of the United States of America, 2013)
In Arabidopsis, lateral root primordia (LRPs) originate from pericycle cells located deep within the parental root and have to emerge through endodermal, cortical, and epidermal tissues. These overlaying tissues place biomechanical constraints on the LRPs that are likely to impact their morphogenesis. This study probes the interplay between the patterns of cell division, organ shape, and overlaying tissues on LRP morphogenesis by exploiting recent advances in live plant cell imaging and image analysis. Our 3D/4D image analysis revealed that early stage LRPs exhibit tangential divisions that create a ring of cells corralling a population of rapidly dividing cells at its center. The patterns of division in the latter population of cells during LRP morphogenesis are not stereotypical. In contrast, statistical analysis demonstrated that the shape of new LRPs is highly conserved. We tested the relative importance of cell division pattern versus overlaying tissues on LRP morphogenesis using mutant and transgenic approaches. The double mutant aurora1 (aur1) aur2 disrupts the pattern of LRP cell divisions and impacts its growth dynamics, yet the new organ’s dome shape remains normal. In contrast, manipulating the properties of overlaying tissues disrupted LRP morphogenesis. We conclude that the interaction with overlaying tissues, rather than the precise pattern of divisions, is most important for LRP morphogenesis and optimizes the process of lateral root emergence.
Gesehen am 24.05.2017